Limits to the discretion of the administrative acts declaring the dismissal of employees with respect to the constitutional and administrative position and the stability privilege in positions of free appointment or removal. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
This document seeks to resolve the question: what are hermeneutically the limits of discretion in the matter of administrative acts related to positions of free appointment and removal, with the discrepancy of the positions of the Constitutional Court and the Council of State in their motivation? by means of the development of the objective of hermeneutically evaluating the limits of the principle of discretionality of administrative acts of declaration of dismissal in the case of positions of free appointment and removal, taking into account the discrepancy of the positions of the Constitutional Court and the Council of State in their motivation. The type of research is descriptive, with a functionalist methodological approach, by means of the case study method and a non-probabilistic sample by convenience. The methodological design is developed by phases; it is concluded that the motivation in administrative acts, the greatest transcendence would be to avoid abuses by the administrative authorities and the discretionality could be more clearly distinguished.
Keywords: Declaration of dismissal; stability privilege; positions of free appointment and removal; administrative acts; limits of discretion